2008
DOI: 10.1103/physrevlett.101.178101
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Contractile Force during Cell Division of Bacteria

Abstract: When a bacterium divides, its cell wall at the division site grows radially inward like the shutter of a camera and guillotines the cell into two halves. The wall is pulled upon from inside by a polymeric ring, which itself shrinks in radius. The ring is made of an intracellular protein FtsZ (filamenting temperature sensitive Z) and thus is called the Z ring. It is not understood how the Z ring generates the required contractile force. We propose a theoretical model and simulate it to show how the natural curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…Third, we found that septum closure is not driven by Z-ring density (FtsZ concentration in the ring) because reduced density in the ΔminC, ΔmatP, and MCI23 strains led to both increases and decreases in septum closure rate, and increased density in the ftsz84 mutant strain did not alter septum closure rate. The Z-ring indeed condenses during the constriction period as previously proposed (35,38,42,43); however, this condensation may be a natural consequence of Z-ring remodeling in response to the gradually reducing septum diameter. Fourth, we found that septum closure cannot be coupled to FtsZ's assembly dynamics during the cell cycle, because three mutations (ftsz84, ΔminC, and ΔmatP) resulted in delayed Z-ring stabilization at midcell but did not lead to systematic changes in the septum closure rate.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Third, we found that septum closure is not driven by Z-ring density (FtsZ concentration in the ring) because reduced density in the ΔminC, ΔmatP, and MCI23 strains led to both increases and decreases in septum closure rate, and increased density in the ftsz84 mutant strain did not alter septum closure rate. The Z-ring indeed condenses during the constriction period as previously proposed (35,38,42,43); however, this condensation may be a natural consequence of Z-ring remodeling in response to the gradually reducing septum diameter. Fourth, we found that septum closure cannot be coupled to FtsZ's assembly dynamics during the cell cycle, because three mutations (ftsz84, ΔminC, and ΔmatP) resulted in delayed Z-ring stabilization at midcell but did not lead to systematic changes in the septum closure rate.…”
Section: Discussionsupporting
confidence: 66%
“…Proposed Z-ring force generation models predict that Z-ring structure would be remodeled in different ways as it contracts [i.e., thickening (46), widening (44), condensing (43), or disassembling (38,39,42)]. To determine whether the Z-ring undergoes such structural remodeling in vivo, we examined Z-ring structures using the single-molecule-based superresolution technique, photoactivated localization microscopy (PALM) (47).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations